RETRACTED: Analytical model of reliability of the freight rail transportation forecasting system - Zhuravleva Natalia; Chechenova Liana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001